A inserção dos egressos da educação popular na escola pública: tensão entre regulação e emancipação - Sonia Maria Alves de Oliveira Reis (2009)
This investigation had as conductive thread the research of the meanings and senses attributed to the school knowledge by the young students and adult egresses from movements of popular education, in continuity or not of studies in the nocturnal regular teaching in Guanambi (BA). The research has the purpose to analyze if there is or there is not a tension between the two pedagogical practices, the emancipative and the regulative, when coming to the Education of Youths and Adults, heiress of the tradition of the popular education, in school education. I looked for verifying and measuring if this tension would be noticed and if the subjects would answer for the continuity or not of the studies. To guide the accomplishment of this study, I highlight Fávero (1983; 2006), Arroyo (2005, 2006), Haddad and Di Pierro (2000), Freire (1987; 1996), Santos (1997, 2000) and others. The understanding of the data is based in the presuppositions of the qualitative approach. From the technician-methodological point of view, I used a field diary constituted of educational spaces and interviews observation, discussing the reasons that take the youth and adults to look for education, to stay at the school and/or to abandon it. The results of the investigation reaffirm there is still necessity of reflection about the organization of the pedagogical work in the youths and adults education; the teachers' manners to work not only with the students, but also with the pedagogical practices of YAE; and the tension movement produced in the groups of several generations and in the teaching and learning process that keeps in itself as much emancipative as regulative potentiality. Finally, this analysis signals the need of an educational formation for teachers to contemplate the particularities of YAE, theoretical-methodological knowledge that contribute to an emancipative educational practice in the spaces and times of Youth and Adults Education.